Quaternary-active thrusts scarps tested as deformation markers by trishear models in the Southern Precordillera of Argentina - Vazquez, Fabricio Rodrigo (2017)
Scarps related to Quaternary-active thrust splays propagating in alluvial bajadas of the Southern Precordillera of Argentina (32°20′) were studied through detailed topographic surveys, in order to understand the reliability of these landforms as deformation markers at an outcrop scale. Geometric parameters of causative structures were used to constrain balanced cross-sections through trishear modelling for shortening estimation and also with the aim of comparing the predicted geometry of these models with the scarp profile. Shortening estimation through retro-deformation of scarps contours was also conducted as an alternative approach for calculating deformation affecting these alluvial surfaces. Results indicate that fold geometries predicted by trishear modelling do not fit with the present scarp shapes, suggesting modifications and slope angle decrease of the front limb. In order to match the modelled folds with the scarp profiles, it is necessary to place constraints to fault parameters, such as ramp angle and tip point position, not compatible with field observations. Trishear models predict shortening values 8 to 15 times larger than those obtained through line retrodeformation of scarp profiles. Therefore, scarp shapes at a mesoscopic scale in the study area, are not considered a reliable deformation marker for shortening estimation of propagating thrusts through an unconsolidated cover.